(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The expediency of such absolute separation rate as income (loss) from core operations and proposed on this basis to calculate the relative cost-effectiveness indicator – profitability of core operations. The effectiveness of operating bakeries in Volyn region in terms of its components: basic operations and other operations. The basic trends and problems in the functioning of enterprises baking industry. It was established that the dynamics of the production of bread tends to decrease activity bakeries characterized by low profitability, and many of them even at a loss